Reasearch on network delay of Internet - Chuan LIN; Hai ZHAO; Yuan-guo BI; Si-yuan JIA (Tongxin xuebao)
Research on the delay of the Internet under marcrotopology plays an important role in comprehension of Inter-net architecture structure and performance. Using effective samples in four different regions authorized by CAIDA Ark and getting network delay, there is little relationship between network delay and communication diameter and the number of the effective paths happening dominant delay is over 70%. The analysis presents that it is dominant delay that affects the relationship between the network delay and the communication diameter. The geographic mapping of the link hap-pening dominant delay supposes that the dominant delay happens frequently in the link across one city in a country. Fi-nally, the conclusion is draw that queue delay is the major composition of the dominant delay for a short range(less than 5 000 km),whereas the propagation delay is the main factor for a long distance(greater than 5 000 km).